The relationship between online vigilance and affective well-being in everyday life: Combining smartphone logging with experience sampling. Issue 5 (3rd September 2021) - Johannes, Niklas; Meier, Adrian; Reinecke, Leonard; Ehlert, Saara; Setiawan, Dinda Nuranissa; Walasek, Nicole; Dienlin, Tobias; Buijzen, Moniek; Veling, Harm
ABSTRACT: Through communication technology, users find themselves constantly connected to others to such an extent that they routinely develop a mind-set of connectedness. This mind-set has been defined as online vigilance . Although there is a large body of research on media use and well-being, the question of how online vigilance impacts well-being remains unanswered. In this preregistered study, we combine experience sampling and smartphone logging to address the relation of online vigilance and affective well-being in everyday life. Seventy-five Android users answered eight daily surveys over five days ( N = 1, 615) whilst having their smartphone use logged. Thinking about smartphone-mediated social interactions (i.e., the salience dimension of online vigilance) was negatively related to affective well-being. However, it was far more important whether those thoughts were positive or negative. No other dimension of online vigilance was robustly related to affective well-being. Taken together, our results suggest that online vigilance does not pose a serious threat to affective well-being in everyday life.